Efficacy and safety of peginterferon alpha monotherapy in Chinese inactive chronic hepatitis B virus carriers. (26th May 2021) - Wu, Fengping; Lu, Rui; Liu, Yixin; Wang, Yikai; Tian, Yan; Li, Yaping; Li, Mei; Wang, Wenjun; Zhang, Xin; Jia, Xiaoli; Dang, Shuangsuo
Abstract: Background & Aims: The effectiveness and safety of peginterferon alpha (peg‐IFN‐α) monotherapy in inactive hepatitis B virus (HBV) carriers (IHCs) have not been fully evaluated. Methods: This observational study prospectively enrolled 298 IHCs in China from 2015 to 2019. Participants were given the right to choose to either receive peg‐IFN‐α monotherapy (treatment group, n = 142) or be monitored without treatment (control group, n = 156) according to their wishes. The scheduled treatment duration was 48 weeks. All participants were followed up to 72 weeks. The main efficacy endpoint was hepatitis B surface antigen (HBsAg) clearance at 72 weeks. Results: Baseline characteristics were similar between both groups. At 72 weeks, intention‐to‐treat analysis showed that the rates of HBsAg clearance and seroconversion of the treatment group were 47.9% (68/142) and 36.6% (52/142), respectively, which were significantly higher than the HBsAg clearance rate of 1.9% (3/156) and the seroconversion rate of 0.6% (1/156) in the control group (both P < .001). Baseline HBV DNA < 20 IU/mL, lower HBsAg levels at baseline, 12 and 24 weeks, alanine aminotransferase elevation at 12 weeks, and greater HBsAg reduction from baseline to 12 and 24 weeks were independent predictors of HBsAg clearance. Generally, the therapy was well tolerated. Only five participants discontinued therapy as a result of peg‐IFNα‐related adverse events. Conclusions: Peg‐IFN‐α monotherapy results in high rates of HBsAg clearance and seroconversion and the treatment is safe for IHCs.